2022
DOI: 10.1111/cbdd.14011
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel ketamine‐inspired derivatives as a protective agent against renal ischemic/reperfusion injury in Wistar rats

Abstract: Renal ischemia‐reperfusion (I/R) injury is a limiting factor for the success of renal grafts and is deemed greatly responsible for the mortality. A novel series of ketamine‐inspired compounds was synthesized and subjected to NF‐ĸB transcriptional inhibitory activity in LPS‐stimulated RAW264.7 cells, where entire set of compounds showed mild‐to‐moderate significant NF‐ĸB transcriptional inhibitory activity (IC50 6.53–67.52 µM). Compound 6d showed highest inhibitory activity among the tested series (IC50 2.62 µM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Anesthetics such as ketamine and propofol have been reported to have antioxidant and protective effects in various organs, especially the kidney and brain (Xing et al 2022;Zhu and Zhang 2022). As mentioned earlier, many studies in the literature examine the harmful or protective effects of many anesthetics on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetics such as ketamine and propofol have been reported to have antioxidant and protective effects in various organs, especially the kidney and brain (Xing et al 2022;Zhu and Zhang 2022). As mentioned earlier, many studies in the literature examine the harmful or protective effects of many anesthetics on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that it exhibits a protective effect against IRI, although the exact molecular mechanisms involved are still unclear [6][7][8][9]. Ketamine has been shown to reduce the generation of pro-inflammatory cytokines, to attenuate induced lipid peroxidation, and also to enhance renal antioxidant status, thus exhibiting a protective effect against renal IRI [6,8]. Ketofol consists of a combination of propofol 0.5mg kg ‫1-‬ and ketamine 0.5mg kg ‫1-‬ .…”
Section: Introductionmentioning
confidence: 99%